2017
DOI: 10.4049/jimmunol.1601880
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Histological Chorioamnionitis Primes the Exometabolomic Profiles of Preterm CD4+ T Lymphocytes

Abstract: Histological chorioamnionitis (HCA) is an intrauterine inflammatory condition increasing the risk for preterm birth, death, and disability due to persistent systemic and localized inflammation. The immunologic mechanisms sustaining this response in the preterm newborn remain unclear. We sought to determine the consequences of HCA exposure on the fetal CD4+ T lymphocyte exo-metabolome. We cultured naïve CD4+ T lymphocytes from HCA-positive and HCA-negative preterm infants matched for gestational age, sex, race,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…It is true that chorioamnionitis is more prevalent in preterm births, but it still complicates up to 4% of term deliveries . Studies focusing on neonatal adaptive immunity have shown that chorioamnionitis exposure amplifies Th17‐ and Th1‐type responses in preterm infants . A study focusing on both innate and adaptive immunity employed a broad transcriptomic approach, using a microarray to evaluate mRNA expression in whole blood of preterm neonates with and without chorioamnionitis exposure .…”
Section: Discussionmentioning
confidence: 99%
“…It is true that chorioamnionitis is more prevalent in preterm births, but it still complicates up to 4% of term deliveries . Studies focusing on neonatal adaptive immunity have shown that chorioamnionitis exposure amplifies Th17‐ and Th1‐type responses in preterm infants . A study focusing on both innate and adaptive immunity employed a broad transcriptomic approach, using a microarray to evaluate mRNA expression in whole blood of preterm neonates with and without chorioamnionitis exposure .…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of amniotic fluid cytokines and chemokines are associated with fetal damage (146)(147)(148)(149), indicating that inflammation can negatively impact the offspring (150,151), namely fetal growth restriction (152). Thus, we followed up our amniotic fluid cytokine determinations with the evaluation of fetal growth parameters.…”
Section: In Vivo T Cell Activation Induces Intra-amniotic Inflammatiomentioning
confidence: 99%
“…Chorioamnionitis exposure has been reported by several groups to drive the emergence of circulating T-effector memory cells (CD4 + CD25 lo CD127 hi ), with a Th1/Th17-like phenotype (126,(137)(138)(139), although one study did not find such a difference (66). Chorioamnionitis also changed the metabolic profile of CD4 + T cells, altering metabolites that are part of the tryptophan catabolism and glutathione detoxification pathway, which could be linked to the enhanced development of a Th1 response (137). Enhanced CD4 production of IL-6 has also been reported (137,140).…”
Section: Fetal Systemic Immune Consequences Of Chorioamnionitismentioning
confidence: 99%
“…Chorioamnionitis also changed the metabolic profile of CD4 + T cells, altering metabolites that are part of the tryptophan catabolism and glutathione detoxification pathway, which could be linked to the enhanced development of a Th1 response (137). Enhanced CD4 production of IL-6 has also been reported (137,140). The mechanisms driving the presence of activated T cells in the context of chorioamnionitis remain unclear, though a recent report showed increased number of activated maternal alloantigen-responsive T cells in preterm infants (141).…”
Section: Fetal Systemic Immune Consequences Of Chorioamnionitismentioning
confidence: 99%